EFEKTIVITAS PENGGUNAAN INFUSA DAUN BENGKAL (Nauclea Orientalis L.) SEBAGAI ANTIDIABETES TERHADAP HEWAN MENCIT - Andy Brata; Lailan Azizah; Dona Muin (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2023)
Background: Bengkal leaves (Nauclea orientalis L.) is a plant that contains flavonoids that act as active substances in reducing blood glucose levels (antidiabetic). The effectiveness of Bengkal leaf decoction (Nauclea orientalis L.) used by the public is still not known as an antidiabetic agent. This research was conducted to test the effectiveness of using Bengkal leaf infusion (Nauclea orientalis L.), used by the community as an antidiabetic test using male white mice that had been induced with alloxan previously. Method: This study used a quasi-experimental study with a static-group comparison design. The experimental animals used were thirty male white mice divided into six groups, namely the negative control group (Tragakan), the positive control group (alloxan), the comparison group (glibenclamide), the Bengkal leaf infusion group with percentages of 10, 20, and 30 Next, testing was carried out by measuring blood sugar levels in mice starting from day 7, 14 to 21. Then one way ANOVA statistical test was carried out to obtain significant results on which day was the most effective. Then Duncan's post hoc test was to determine the best concentration with an effect close to 5 mg of glibenclamide so that it would be known whether Bengkal leaf infusion (Nauclea orientalis L.) is effective as an antidiabetic. Later, in the end, find out whether the community can use Bengkal leaf infusion as an antidiabetic drug. Results: After statistical tests, it was proven that Bengkal leaf infusion with a percentage of 10, 20, and 30 effectively reduced blood sugar levels in mice with a significance of p = 0.000. The best levels affecting the comparison on day 21 are 20 and 30 percent infusions. Conclusion: There is effectiveness in using Bengkal infuse leaf infusion (Nauclea orientalis L.) as an antidiabetic so that the community is an antidiabetic drug.